Pengaruh pencapaian kepuasan konsumen rumah makan berdasarkan kesan kualitas produksi dan harga - Eli Retnowati; Rahayu Mardikaningsih; Didit Darmawan; Ella Anastasya Sinambela (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
The increasing development of the restaurant industry causes competition between business people, each business actor. This study was conducted to analyze and discuss the role of product quality impressions and price impressions on consumer satisfaction who visited the